Ionospheric effects of recent stratospheric sudden warmings - Goncharenko, L. (2011)
Recent studies have shown large variations in low-latitude ionospheric parameters occurring after stratospheric sudden warming events. We use observations of vertical ion drift from Jicamarca ISR and GPS total electron content data in the Western Hemisphere for winters of 2008-2009 and 2009-2010 to illustrate main features of ionospheric changes related to stratospheric sudden warmings. The common feature in all events is the increase in the electron density during the morning hours and the decrease in the afternoon, related to amplification of 12-hour signature in low-latitude vertical ion drifts. This feature persists for several days after the peak in stratospheric temperature. The observed phenomena is related to quasistationary planetary waves, which have a high amplitude level prior to the stratospheric warmings. Non-linear interaction of planetary waves with tides leading to increase in tidal amplitudes in the low latitude lower thermosphere and modulation of E-region electric field with subsequent mapping to the F-region is thought to be the primary mechanism responsible for the observed ionospheric response. We investigate the characteristics of ionospheric oscillations with planetary wave periods between 2 and 30 days and in a wide range of latitudes in context of variations in stratospheric parameters.